Isolation of a Series of Fatty Acid Components of Ongokea gore Seed (Isano) Oil and their Detailed Structural Analysis. Issue 3 (25th December 2014) - Ntumba, Joséphine K.; Collard, Laurent; Taba, Kalulu M.; Robiette, Raphaël
Abstract: The total oil production capacity of isano oil is estimated at about 10, 000 tons annually. Previous studies of this oil revealed that it is rich in fatty acids including a conjugated diyne moiety. This makes isano oil an excellent candidate for sustainable applications development. However, only a few of its fatty acids have been isolated and identified so far. In this study, we have reinvestigated this oil by characterizing its physicochemical properties and isolating several of its fatty acids as ethyl esters for their detailed structural analysis and identification. Six ethyl esters of fatty acids constituting isanic oil were isolated by flash column chromatography and semipreparative HPLC. The detailed structural analysis of these fatty acid esters by infrared, high resolution, mass spectroscopy, and nuclear magnetic resonance (1‐D and 2‐D) allowed determining unequivocally their chemical structure. The main fatty acid component of the oil (35.7 %) was identified as isanic acid. Four minor acids were found to possess also two conjugated triple bonds, while the sixth fatty acid does not contain carbon–carbon triple bonds nor double bonds but possessed a cis epoxide function. Results obtained in this study are currently being used to explore potential applications of isano oil.